(3TQM GdQSGdI GdfGUMI aj GdOdGFd GdQGSNIs - (3GdefUhQ HGddg (B- (3GdefUhQ , YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI Gdjefj, GdRjOj GdefUhQ HGddg,J (B614 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi bgQ SdWGf Gdedhc HSdWGfg hYdG Ydi TCf GdLHGHQI TCfg s
(3BNQgG (B:s
(3adG MGLI dEYGOI PcQg GfJgjfG Edi BNQ TQM GdQSGdI GdfGUMI hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg GdWjHjf GdWGgQjf s
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B213s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(226 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds